Control of Thickness and Chemical Properties of Atomic Layer Deposition Overcoats for Stabilizing Cu/γ‐Al2O3 Catalysts. Issue 12 (25th September 2014) - O'Neill, Brandon J.; Sener, Canan; Jackson, David H. K.; Kuech, Thomas F.; Dumesic, James A.
Abstract Whereas sintering and leaching of copper nanoparticles during liquid‐phase catalytic processing can be prevented by using atomic layer deposition (ALD) to overcoat the nanoparticles with AlOx, this acidic overcoat leads to reversible deactivation of the catalyst by resinification and blocking of the pores within the overcoat during hydrogenation of furfural. We demonstrate that decreasing the overcoat thickness from 45 to 5 ALD cycles is an effective method to increase the rate per gram of catalyst and to decrease the rate of deactivation for catalysts pretreated at 673 K, and a fully regenerable copper catalyst can be produced with only five ALD cycles of AlOx. Moreover, although an overcoat of MgOx does not lead to stabilization of copper nanoparticles against sintering and leaching during liquid‐phase hydrogenation reactions, the AlOx overcoat can be chemically modified to decrease acidity and deactivation through the addition of MgOx, while maintaining stability of the copper nanoparticles.